Local Government Strategy in Overcoming Extreme Poverty in Pandeglang Regency (Study in Sindangresmi District) - Romli, Ombi; Khoirunisa, Khoirunisa (Educational Studies and Research Journal, 2024)
This study aims to analyze the strategy of local governments in overcoming extreme poverty in Sindangresmi District, Pandeglang Regency, which is one of the areas with the highest extreme poverty rate in Banten Province. The focus of the research is directed at local governments' efforts to overcome the socio-economic problems of the extreme poor, including the identification of supporting factors, inhibitions, and the effectiveness of the implementation of the strategies implemented. The research method used is qualitative with a descriptive approach, through in-depth interviews with local government officials, sub-district officials, and program beneficiaries. The data was also strengthened by documentation studies and field observations. The results of the study show that local government strategies in combating extreme poverty are carried out through three main approaches, namely reducing the burden of expenditure on the poor, increasing income, and reducing pockets of poverty. Supporting factors for this strategy include policy support, collaboration between agencies, and active community participation. However, its implementation still faces obstacles such as budget limitations, low human resource capacity, and regional geographical challenges. This study recommends the need to strengthen cross-sector coordination, increase the capacity of the apparatus, and optimize the budget so that extreme poverty reduction programs can be more effective and sustainable.